Implementasi Kebijakan Peraturan Walikota Batu Nomor 56 Tahun 2020 Berbasis Collaborative Pentha Helix (Studi pada Sektor Pariwisata Kota Batu) - Rahman, Zahidur; Rozikin, Mochammad; Sentanu, I Gede Eko Putra Sri (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
Almost all parts of the world, in the last 2 years, have been faced with the spread of COVID-19 originating from Wuhan, China, which then developed rapidly to various countries, including Indonesia. COVID-19 has an impact on all sectors, especially the tourism sector in Batu City. As an effort to protect its citizens, the Batu City Government issued a policy in the form of Mayor Regulation Number 56 of 2020 concerning Guidelines for the Prevention and Control of Corona Virus Disease 2019 in the Transitional Status of Emergency to Recovery. The results of the study show that the implementation of the Mayor's Regulation Number 56 of 2020 concerning Guidelines for the Prevention and Control of Corona Virus Disease 19 (COVID-19) in the Transitional Status of Emergency to Recovery, especially for the tourism sector in Batu City, has been carried out well from the policy implementation model. Van Matter and Van Horn. The collaboration process of Penthahelix stakeholders in the implementation of Perwali 56/2020 takes place in synergy and mutually reinforcing which involves government actors up to the village level, RW and RT, entrepreneurs, communities, academics and the media.